2007
DOI: 10.1103/physrevlett.98.076601
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Early Stages of Pentacene Growth by Supersonic Molecular Beam Deposition

Abstract: The key role of the pentacene kinetic energy (Ek) in the early stages of growth on SiOx/Si is demonstrated: islands with smooth borders and increased coalescence differ remarkably from fractal-like thermal growth. Increasing Ek to 6.4 eV, the morphology evolves towards higher density of smaller islands. At higher coverage, coalescence grows with Ek up to a much more uniform, less defected monolayer. The growth, interpreted by the diffusion mediated model, shows the critical nucleus changing from 3 to 2 pentace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 21 publications
3
73
0
Order By: Relevance
“…The fact that in our case the highest frequencies lattice modes at 122 and 132 cm −1 have intensity comparable to that of the intra-molecular modes ( Figure 5) means that the films are characterized by a high degree of lateral order. This finding is in agreement with experiments showing that SuMBD-grown films grow layer by layer and have larger single crystalline domain in comparison with high-vacuum molecular beam deposition [29]. On the other hand, phonons below 80 cm −1 present dispersion along k(0, 0, k), i.e., normal to the ab plane [23].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The fact that in our case the highest frequencies lattice modes at 122 and 132 cm −1 have intensity comparable to that of the intra-molecular modes ( Figure 5) means that the films are characterized by a high degree of lateral order. This finding is in agreement with experiments showing that SuMBD-grown films grow layer by layer and have larger single crystalline domain in comparison with high-vacuum molecular beam deposition [29]. On the other hand, phonons below 80 cm −1 present dispersion along k(0, 0, k), i.e., normal to the ab plane [23].…”
Section: Resultssupporting
confidence: 91%
“…The apparatus is essentially the same as previously described [29]. The raw material bought from Sigma-Aldrich Italy (Milan, Italy) ( 99.995% of purity) was used after outgassing the source at a temperature slightly lower than the pentacene sublimation temperature.…”
Section: Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for SuMBD grown pentacene thin films, it is more straightforward to change the grain size by tuning the pentacene kinetic energy (E k ) within the molecular beam. In recent studies on pentacene nucleation and growth, we showed how the pentacene critical nucleus size changes with the kinetic energy of the impinging molecules during the early phase of pentacene growth on SiO 2 /Si [18]. Here we extend this investigation to better understand the correlation between E k and island morphology.…”
Section: Introductionmentioning
confidence: 76%